2011
DOI: 10.1002/jcp.22413
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the fluorescent acrosomal matrix and its fate in fertilization in the water strider, Aquarius remigis

Abstract: Animal sperm show remarkable diversity in both morphology and molecular composition. Here we provide the first report of intense intrinsic fluorescence in an animal sperm. The sperm from a semi-aquatic insect, the water strider, Aquarius remigis, contains an intrinsically fluorescent molecule with properties consistent with those of Flavin Adenine Dinucleotid (FAD) which appears first in the acrosomal vesicle of round spermatids and persists in the acrosome throughout spermiogenesis. Fluorescence recovery afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The underlying grayscale image represents the intensity ratio between maximum and minimum fluorescence (black for ratio = 1, white for ratio = 4) measured at each location. Reprinted with permission from Miyata et al ().…”
Section: Lc‐polscopementioning
confidence: 99%
See 1 more Smart Citation
“…The underlying grayscale image represents the intensity ratio between maximum and minimum fluorescence (black for ratio = 1, white for ratio = 4) measured at each location. Reprinted with permission from Miyata et al ().…”
Section: Lc‐polscopementioning
confidence: 99%
“…The underlying grayscale image represents the intensity ratio between maximum and minimum fluorescence (black for ratio ¼ 1, white for ratio ¼ 4) measured at each location. Reprinted with permission from Miyata et al (2011). remarkable molecular choreography of septin assemblies involved in cell division was first discovered in the yeast bud neck (Vrabioiu and Mitchison, 2006) and then revealed in other cell types (DeMay et al, 2011a).…”
Section: Molecular Reproduction and Developmentmentioning
confidence: 99%
“…FRAP has also been used to monitor the incorporation of a flavin adenine dinucleotide (FAD)‐associated protein into the acrosomal matrix of sperm from the water strider, Aquarius remigis , during spermatogenesis and spermiogenesis (Fig. ) (Miyata et al, ). Along with fluorescence polarization microscopy, this study demonstrated that, following meiosis, the FAD‐containing protein rapidly accumulates into a rigid matrix that ultimately extends as a ∼2,500 μm helical structure from base to tip.…”
Section: Fluorescence Recovery After Photobleachingmentioning
confidence: 99%
“…FRAP has been applied to many developmental studies, including the original studies monitoring the behavior of acetylcholine receptors in chick myotubes (Axelrod et al, 1976b); the extent of lipid mobility in gametes (Wolf and Voglmayr, 1984;Wolf et al, 1986Wolf et al, , 1988; the distribution and dynamics of galactosyltransferase on the surface of mouse sperm (Cardullo and Wolf, 1995) and ADAM1/ ADAM2 on guinea pig sperm (Hunnicutt et al, 2008); and the formation of an acrosomal matrix during spermatogenesis in water strider sperm ( Fig. 3) (Miyata et. al., 2011).…”
Section: Applications Of Frap In Reproductive and Developmental Biologymentioning
confidence: 99%
See 1 more Smart Citation